Análise dos Projetos Pedagógicos de Curso do PROEJA-FIC no âmbito do IFSP, à luz da Pedagogia Crítico Emancipatória - Santos, Renata Reis dos (Universidade Federal de São Carlos, 2021)
This dissertation brings analysis of the Pedagogical Course Projects of the National Program for the Integration of Vocational Education with Basic Education in the Modality of Education of Youths and Adults - Initial and Continuing Education, recognized by the acronym PROEJA-FIC at the Federal Institute of Education , Science and Technology of São Paulo (IFSP), the insight Critical Emancipatory Pedagogy. This study has a central theme the Curricular Policies and the presence of Paulo Freire's Pedagogy in the Pedagogical Course Projects (PPC). The questioning about the construction of a critical curriculum for PROEJA-FIC raised two questions: The first was to investigate whether the PROEJA-FIC Base Document, which was developed by the Ministry of Education (MEC) in 2007, had Freire's influences; and the second was to verify whether these Freirean influences present in the Base Document were reflected in the PROEJA-FIC PPCs in force within the scope of the IFSP. In this sense, the main objective of the research included analyzing Freirean categories in PPCs. To answer these questions and consolidate the proposed objectives, a review of the available literature and documentary analyzes were carried out. The literature review was based on authors who defend a Critical Curriculum, among which the following stand out: Paulo Freire, Michael Apple, Henry Giroux. This study made it possible to understand the interfaces that permeate the construction of a critical curriculum and the establishment of Freire's categories: Dialogue, Interdisciplinarity and Praxis; that supported the analysis of the PPCs. The results indicated that the Base Document (2007) has influences from Freirean Pedagogy, however the PROEJA-FIC PPCs are distant from a critical educational perspective and have characteristics geared to technicality. After realizing that the PPCs did not dialogue with Critical Emancipatory Pedagogy, the research made considerations about the elements that should be considered for a curricular restructuring with a view to emancipation and humanization.
Analysis of Pedagogical Projects of Course PROEJA-FIC within the scope of IFSP, the insight of Critical Emancipatory Pedagogy.
Keywords: Critical Curriculum; Educação Profissional e Tecnológica; Educação de Jovens e Adultos; Paulo Freire; PROEJA-FIC; Vocational and Technological Education; Education of Youths and Adults; CIENCIAS HUMANAS::EDUCACAO::CURRICULO